Determinants of Promoting Assisted Delivery in the Lagdo Health District in Northern Cameroon - Abdoulahi Kami; André Nkondjock; Antoine Socpa (Journal of Epidemiology and Public Health, 2024)
Background: Discrepancies in findings on assisted delivery (AD) in the Northern Cameroun persist. In order to reduce maternal mortality, it is hypothesized that specific determinants may help promote the use of AD. This study aimed to assess the possible association between these determinants and AD.Subjects and Method: A cross-sectional study was carried out on 1,175 postpartum women, in the Lagdo health district from May 10th to June 5th, 2023. A three-stage cluster sampling technique was used. Independent variables included the factors related to AD. The dependent variable was the use or no use of AD. A validated questionnaire was employed to gather information. Data analysis was performed with SPSS software version 25. Frequencies, odds ratios (OR), and corresponding 95% confidence intervals (CI) were calculated. The statistical significance was 0.05.Results: The prevalence of AD was 43.9%. After adjustment for age, educational attainment, and parity, a direct association was detected between AD and funded delivery fees (OR=2.5; 95%CI= 1.95 to 3.40; p<0.001), and the presence of motorcycle taxi driver (OR=1.70; 95%CI =1.31 to 2.19; p<0.001). An inverse relationship was observed between AD and distance to health centers (OR= 0.32; 95%CI = 0.18 to 0.58; p<0.001), and lack of community leaders' involvement (OR=0.45; 95%CI = 0.31 to 0.67; p<0.001).Conclusion: Our findings suggest funding delivery fees, reducing distance to health facilities, and sensitizing women by community leaders may help promote AD.